Social and spatial mobility along the Kuiseb River in the Namib Desert, Namibia - Dentlinger, Ursula (University of Cape Town, 2016)
Bibliography: pages 220-231. === This study seeks to explain the unusually high rate of circulation of individuals between local domestic units of the rural settlements along the Kuiseb River as well as between these and domestic units in the closest urban centre. It is argued that these movements form part of a general state of flexibility of personal relationships, which subsequently affects household composition. An explanation for this flexibility is suggested in terms of one strategy of survival pursued by relatively poor individuals, which involves the sporadic attachment by poorer individuals to relatively more economically stable relatives. As these attachments, whether residential or not, are of short duration, they produce rapid and unpredictable changes to the composition of existing households. Material is presented of three areas of social life illustrating these sporadically shifting alignments. These areas are subsistence relations, conjugal relations and parent-child relations. These examples of sporadic shifts of domestic alignments are contrasted with a few examples where households were seen to show facets of cyclical changes in their social composition. Evidence suggests that these few households were headed by economically secure individuals, who also reflect a considerable stability in their residence. The question is raised whether a cyclical development of domestic groups can be recorded in situations as flexible and variable as those along the Kuiseb River. This in turn raises the issue of the usefulness of a framework postulating such a development.